Job loss, disability insurance and health expenditures - Anikó Bíró; Peter S. Elek (Hungarian Academy of Sciences, Institute of Economics, 2019)
We analyse the causal effect of job loss on disability insurance enrolment on a five-year horizon and the implications on health expenditures. Using individual level administrative panel data from Hungary, we follow individuals displaced due to a mass lay-off and compare their labour force status to non-laid-off individuals with similar employment and health history, chosen with propensity score matching. According to our estimates, being laid off increases the transition probability to disability by 50% (or 1.4% points) in four years, and half of the excess transitions occur within the first year. We find a greater than average effect among older individuals and those who were in worse health before. Outpatient, inpatient and pharmaceutical expenditure increases 3.5-4 times when a laid-off individual takes up disability benefit, and decreases slightly afterwards, but does not reach the pre-disability levels. This health expenditure pattern resembles that observed around the diagnosis of previously undetected chronic diseases, such as diabetes or hypertension, but genuine health shocks may also be present. The increase in health expenditure corresponds to 20-25% of the additional disability payments in the medium term.
Keywords: C23; I12; I38; J63; 330; administrative panel data; disability insurance; displacement; health expenditures